ESSENTIALITY OF FLUID INTAKE BY THE HUMAN BODY - Chatterjee, Bandana (International Journal of Clinical and Biomedical Research, 2017)
Like hunger thirst is also an important factor of human body. It is important for maintaining fluid homeostasis within the body. It is a perception that creates the urge for all humans for drinking fluids. It aids in maintaining body fluid homeostasis which is essential for survival. The quest of thirst can arise due to any one of the reasons such as habitual, cultural etc. When the body loses water it is not the case that equal amount will be lost from each of the fluid spaces - extracellular and intracellular. KEYWORDS: Fluid homeostasis; Daily requirement; Non-communicable diseases.